The Relationship of Professional Ability and Management System Construction Under Mediation of Administrative Expert Role Cognition - Hsien-Yu, Shun (Journal of Organizational Psychology, 2021)
This research explored the relationship among human resource practitioner professional ability, administrative expert role cognition and the degree of human resource management system construction. The paper is based on a questionnaire survey. Data collected from the foreign investment enterprise list in Shanghai city, China. Eight hundred questionnaires were sent out, 223 valid questionnaires were returned (27.88%). The results show that there is a significant influence between the: (1) Professional ability of human resource practitioners and the degree of human resource management system construction and (2) administrative expert role cognition of human resource practitioners and human resource management system construction and also that (3) administrative expert role cognition has a partial mediating effect between professional ability and the degree of human resource management system construction. The originality and value of this study is one of very few studies which have investigated that administrative expert role has the mediating effect between the human resource practitioners professional ability and human resource management system construction.